Analisis Faktor-Faktor yang Mempengaruhi Kebijakan Hutang Perusahaan Subsektor Batu Bara yang Terdaftar di Bursa Efek Indonesia - Novita Fatmawati; Nurjanti Takarini (Universitas Batanghari Jambi, 2022)
A company has a goal that is to experience continuous growth by getting maximum income and profit so that survival in a company can run well. In achieving this goal, large funds and capital are needed to support all activities within a company. Funds are divided into two categories, namely internal funds and external funds. The debt to equity ratio indicator is used in this study with debt policy as the dependent variable. This study aims to analyze the effect of business risk, asset structure, firm size and profitability on the debt policy of coal companies. In this research, using multiple linear regression analysis method with SPSS 25 program to process the data. The data used is secondary data which is the annual financial report of coal subsector companies on the Indonesia Stock Exchange in 2018-2020. The observation data used are 66 data, and there are 5 data outliers, so the total data is 61. The results of this study indicate that business risk has a positive and significant influence on debt policy, asset structure and firm size have no significant effect on debt policy, and profitability have a negative and significant impact on debt policy. The conclusion from the discussion is that high business risk contributes to an increase in debt. Meanwhile, asset structure, firm size and high profitability contributed to the decrease in debt.